Viruses infecting daphne in New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Horticultural Science - Forster, Richard LLewellyn (Massey University, 1974)
The genus Daphne belongs to the Thymelaeaceae and contains both evergreen and deciduous shrubs which produce attractive, highly fragrant flowers. Plants are neat and shapely and seldom grow more than 3-4 feet high, fitting well into rock gardens or herbaceous borders. A large number of species of this very popular ornamental are grown in New Zealand, the most common of which is Daphne odora Thunb. This latter species contains several cultivars and one (Daphne odora 'Leucanthe') is almost ubiquitous at least in the North Island. Its importance is illustrated by the fact that several nurseries visited during the study cited production figures for Leucanthe of between 5,000 and 12,000 specimens per annum and one firm has also entered the export trade. Daphne burkwoodii Turrill and Daphne cneorum L. are two other species which are also commonly grown in N.Z. [FROM PREFACE]
Keywords: Daphne -- Diseases and pests; Virus diseases of plants